Aplikasi Pupuk Kompos Hasil Fermentasi Limbah Ternak Ayam Pada Tanaman Sawi Hijau (Brassica Juncea) - Kisen, Kisen Agian Pappa; Debianti, Debianti; Limbongan, Yusuf L.; Tandirerung, Willy Yavet; Karuru, Sakti Swarno (Median : Jurnal Ilmu Ilmu Eksakta, 2025)
This research aims to analyze the effect of organic fertilizer from chicken waste compost mixed with roasted husks and runny water on the quality of the fertilizer and the growth of green mustard greens (Brassica juncea). The method used was a randomized block design (RAK) with treatments consisting of K0 = Control, K1 = 10 Tons/Ha (50 gr/polybag), K2 = 20 Tons/Ha (100 gr/polybag), K3 = 30 Tons/Ha (150 gr/polybag), and K4 = 40 Tons/Ha (200 gr/polybag). Each treatment consisted of 75 plants divided into 5 plots, with each plot containing 15 plants. The research results showed that compost fertilizer with a concentration of 100 gr/polybag provided the best effectiveness in increasing the growth of mustard greens, as seen from plant height (33.63), number of leaves (11.67), and plant weight (157.67), compared to other treatments. This research also provides solutions for managing livestock waste and supporting sustainable agriculture. Using compost is safer than chemical fertilizer, can maintain moisture in plant roots, and does not damage the environment.